Contemporary and seen according to Ibn Wasel through his book Mufarrej Al-Kroub in the news of Bani Ayyub - سليمان بلال; مرفت اسكندر; زينب خير الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The twelfth century AH witnessed a widespread prosperity And a great maturity with the blogging and history movement, in which a sect appeared from The greatest authors and thinkers in addition to poets and historians who They were distinguished by their good cultural composition, in terms of their education And literature and Quranic studies, the heritage of Arabic literature, slaughter and origins Religion and the hindrance, as well as the historians of utilitarian individuals They were, imams, preachers or judges, as they worked in the tile departments And writing Correspondence, and collection Al - Nasous. They took diplomatic duties And they advised the rulers From Ibn Wasel was among A busy crowd, from thinkers And historians, as it is considered one of the Ayyubid states Until its end, and if there is those who preceded it in history for this country. However, it was not dated to this state in particular, but rather within it on dates In general, and when Ibn Wasil was a contemporary of the end of this state and this is this He managed to be familiar with the details of this country For anyone it is. The study aims to shed light on what Ibn Wasel left from material Scientific for the Ayyubid state in his book Moufarj Al -Karaoub, which is his contemporary And he guided him to events what The study dealt with a brief overview of Ibn Wasil’s views in his book Mufarraj Al -Karaoub, during the Ayyubid rule, which witnessed two dangers The Islamic presence in the Arab Islamic East, represented by attribution The Franks and the Mongol invasion, as well as the study clarified And contemporary with Ibn Wasel, his trips and its impact on his observations is nature Watch materials, the scientific value of these views.